Discriminatory models’ adaptation in small and medium sized health care entities - Szewieczek, Aleksandra; lisicki, Bartłomiej (Serbian Journal of Management, 2019)
The article presents the utilization of discriminatory analysis in small and medium sized hospitals. The discriminatory models are used to estimate the probability of researched hospitals bankruptcy. The financial distress is tested with two popular models, one foreign (the Altman Z’’Score Model) and one domestic (the Mączyńska Model). The authors also construct their own model, adapted to the specification of medical activity. The results indicate that the author’s model is much more suitable for the small and medium sized hospitals, as the rate of prediction is highest. It may indicate that in the health care sector, particularly in small and medium sized companies, different phenomena occur, which affect these companies’ financial distress. Despite this, this study indicates that the proposed model is one of the useful tools for their evaluation, especially when combined with other financial as well as non-financial tools. Finally, it was possible to verify the hypothesis that it is possible to create a discriminatory model dedicated to SMEs hospitals, which results are more accurate than using different, not adjusted to health care sector specifics, discriminatory models.